Determination of cadmium in vegetables by sequential injection analysis method using 8-hydroxyquinoline as complexing agent - Kanokwan Chaiyasing (2019)
© 2019, Chiang Mai University. All rights reserved. In the present study, a novel and eco-friendly sequential injection analysis (SIA) system with spectrophotometric detection was developed for determination of Cd(II) in vegetable samples. The method is based on the reaction of 8-hydroxyquinoline with Cd(II) as a less-toxic complexing agent in H2SO4 solution, resulting in a light yellow colored complex monitored at 360 nm. The SIA parameters were optimized to obtain the best sensitivity and minimum reagent consumption. Under the optimum conditions, linear calibration graphs over the ranges of 0.04-1.0 mg L-1 and 1.5-5.0 mg L-1 were established. Due to the limitation of Beer’s law, the maximal absorption of the complex was observed at Cd(II) concentration of 1.0 mg L-1. Above which the absorbance decreased with curvature and started to be linear with low slope. The useful calibration graph for Cd(II) in vegetable sample was the first one. The limit of detection was 0.01 mg L-1, with the intra-day and inter-day precisions were less than 1.5%. The proposed method was successfully applied to the determination of Cd(II) in different vegetable samples (chinese kale, false pakchoi, cabbage, lettuce, cucumbers, coriander, water convolvulus, yard long bean, tomatoes, and potatoes) after appropriate sample pretreatment. The obtained results were in good agreement with those obtained by the ICP-MS standard method, verified by the student t-test at the 95% confidence level.